Microbial Production of the Off-Flavor Geosmin in Tilapia Production in Brazilian Water Reservoirs: Importance of Bacteria in the Intestine and Other Fish-Associated Environments - Lukassen, Mie B.; de Jonge, Nadieh; Bjerregaard, Sabine M.; Podduturi, Raju; Jørgensen, Niels O. G.; Petersen, Mikael A.; David, Gianmarco S.; da Silva, Reinaldo J.; Nielsen, Jeppe L. (Frontiers in Microbiology, 2019)
Aim: To determine major sources of microbially produced geosmin in the commercially important aquaculture fish species tilapia. Methods and results: Abundance and composition of geosmin-producing bacteria in water and fish biosphere (intestine, digesta, and fins) of Nile tilapia (Oreachromis niloticus) raised in net cages in Brazilian freshwater farms were examined. By combining qPCR of the geosmin synthase geoA gene and 16S rRNA gene amplicon sequencing to identify potential geosmin-producing organisms, we observed that the proportion and composition of geosmin producers appeared to be rather similar in the water, digesta, intestinal mucous, and on skin, making up about 0.1- 0.2 % of the total bacterial densities. A high proportion of Cyanobacteria and other putative geosmin producers affiliated to the Actinomycetales were identified in the intestinal mucous layer. The main uptake site for geosmin in fish is traditionally assumed to be through the gill surface, but the present results suggest that uptake by the intestinal tract may represent a major source of geosmin uptake in fish. Conclusions: The high abundance of geosmin-producing bacteria in the intestinal mucous layer and digesta may indicate that the digestive system in fish is an important, but hitherto overlooked, source of geosmin and likely other off-flavours in fish. Signiﬁcance and impact of Study: Tainting of fish by microbially produced off-flavours spoils fish quality and lowers consumer preferences for aquaculture-produced freshwater fish. Our results highlight the potential for the application of probiotic microorganisms for management of the intestinal microflora to improve the fish quality.